How Did Human Activity and Climate Change Influence Animal Exploitation During 7500–2000 BP in the Yellow River Valley, China? - Du, Linyao; Ma, Minmin; Lu, Yiwen; Dong, Jiajia; Dong, Guanghui (Frontiers in Ecology and Evolution, 2020)
The mid-late Holocene witnessed the rapid development of Neolithic and Bronze cultures in the Yellow River Valley (YRV) of northern China. Spatio-temporal patterns of plant utilization during this period and its influencing factors have been intensively discussed, whereas the variation in animal exploitation in relation to climate change and human activities has not been adequately studied. In this paper, we reviewed zooarchaeological data obtained from 38 Neolithic and Bronze sites in YRV, and compared them with paleoclimate and archaeological records, to reconstruct the trajectory of animal utilization in this area between 7500–2000 BP and discern the influencing factors driving it. The results revealed that animal exploitation was mainly sourced from wildlife between 7500 BP and 6000 BP, shifting to omnivorous livestock sources in the period of 6000–4000 BP except in the northeast Tibetan Plateau. During 4000–2000 BP, however, omnivorous and herbivorous livestock had come to dominate humans’ subsistence on animals, which nonetheless showed substantial spatio-temporal variation in the YRV. Further analysis suggests that animal exploitation in the Neolithic and Bronze YRV were both directly affected by human activities, while climate change might have influenced the environment surrounding human settlements and, indirectly, their choice of animals to exploit. This work provides new perspectives for exploring the changing patterns of human–environment interactions in the YRV during the mid-late Holocene.